Conscience Clauses and the Placement of Children (Journal of Law and Family Studies; Vol 15 No 1 (2013), 2014)
Adoption is a creature of statute. There is neither a fundamental right to adopt nor to be adopted and states have much discretion with respect to the contents of their adoption laws. Nonetheless, that discretion is not unlimited. Both the United States Constitution and federal statutes limit states with respect to how they regulate adoption, though the contours of those limitations are not clearly laid out. Those contours are now becoming more contested, and the courts will likely be forced to clarify the degree to which states with discretion with respect to the contents of their adoption regulations and statutes. Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;}